Otto se presenta para presidente - Wells, Rosemary 1943- (Scholastic en español, 2008)
While the popular Tiffany and athletic Charles make increasingly outrageous promises in their campaigns for President of Canine Country Day School, Otto quietly enters the race, vowing only to try to do what students really want